Unraveling Age-Related Declines in Syntactic Processing: Insights from Research - Li, Yiran; Gao, Peixiao (Journal of Psychology and Behavior Studies, 2024)
As the field of gerolinguistics receives increasing attention, research on language in older adults has expanded globally. This article explores the complexity of syntactic processing in older adults, examining studies related to language comprehension and production in the elderly. With aging, the brain undergoes a trend of developmental decline, resulting in structural changes, particularly in key regions involved in language processing. While some studies indicate that syntactic processing remains relatively intact with age, others suggest declines in performance, including slower response times and increased error rates. Methodological advances using functional magnetic resonance imaging (fMRI) and event-related potentials (ERP) have revealed the neural substrates underlying age-related changes in syntactic processing. Despite facing numerous challenges, compensatory mechanisms play a significant role in maintaining language comprehension in older adults. The article concludes by outlining future research directions, emphasizing the necessity of interventions to enhance syntactic processing abilities in older adults. By employing interdisciplinary approaches and advanced neuroimaging techniques, researchers can better understand the dynamic nature of language processing across the lifespan, ultimately contributing to promoting healthy cognitive aging and improving the quality of life for older adults.